UKURAN RISIKO BERDASARKAN PRINSIP PENENTUAN PREMI : PROPORTIONAL HAZARD TRANSFORM - Aprida Siska Lestia (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2014)
The problem that will be discussed in this paper is an analysis of one type of risk measure that determines it based on the principle of premium determination (premium-based risk measures), namely Proportional Hazard (PH) transform, both in the form of basic concepts and their properties. It will then assess the size of the risk for some of the total data distribution models of insurance claims that are generally heavy tailed. Where the assessment process is done simulated using Monte Carlo method and recursive method. The discussions made for the distribution of total claims will only be limited to the claims of distributed gamma, Weibull, Pareto, lognormal, and loglogistic and distribution of many claims used in the form of binomial, binomial negative and Poisson.